Seed fate : predation, dispersal and seedling establishment (CABI, 2005)
This book presents current knowledge of seed fate, in both natural and human-disturbed landscapes, from various regions of the world. Habitats considered range from mountains and arid deserts in the temperate zone, to savannas and lowland rain forests in tropical regions. Particular attention is paid to plant diversity conservation when seed removal is affected by factors such as hunting, habitat fragmentation or intensive logging.